Effects of allitridi on intracellular Ca2+ concentration in isolated rat brain cells - Ma Xiao-hong; Pan Xin-xin; Liu Tian-pei (Acta Pharmacologica Sinica, 2016)
AIM: To study actions of allitridi extracted from garlic on intracellular calcium in isolated rat brain cells. METHODS: Brain cells were isolated from newborn rat brain with Fura 2-AM measurements of intracellular Ca2+ concentration ([Ca2+]i). RESULTS: Allitridi 1-100 mumol.L-1 concentration-dependently blocked increases of [Ca2+]i caused by potassium chloride and sodium glutamate (Glu) with IC50 of 59.7 and 69.9 mumol.L-1 respectively. Allitridi 100 mumol.L-1 blocked norepinephrine (Nor)-induced [Ca2+]i elevation. CONCLUSION: Allitridi is an effective agent for blocking the [Ca2+]i increase caused by potassium chloride, Nor and Glu.